Exploring Mn+/silicalite-1 as a catalyst for Biginelli reaction to produce dihydropyrimidinone derivatives - Suwito, Hery; Zulianto, Lutfan; Haq, Kautsar Ul; Abdulloh, Abdulloh; Erwanto, Erwanto; Pebriani, Fitria; Jihadi Al, Arjun N.; Hin, Taufiq Yap Y. (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2024)
A series of Mn+/silicalite-1 was prepared to be used as a Lewis acid heterogeneous catalyst for a one-pot multicomponent Biginelli reaction. The catalysts were characterized by FTIR, XRD, NH3-TPD, and BET. The mesoporous catalysts possess a pore diameter of 13.83 nm (138.3 Å), a surface area of 282.43 m2/g, and a pore volume of 0.98 cm3/g, which can facilitate the transport of reactants and products smoothly during the catalytic process. Besides the acidity of the catalyst, the maximum temperature of NH3-desorption plays an important role in the catalytic activity. Cr3+/silicalite-1 showed the most active catalyst, while Zn2+/silicalite-1 showed the most selective one. Besides DHPM derivatives as a major Biginelli product, C6-styril of DHPM and Knoevenagel products were isolated if the reaction was conducted using Cr3+/-and Fe3+/silicalite-1. Catalyst Cr3+/silicalite-1 can be used to produce DHPM attaching various substituents and showed a green catalyst potential due to its reusability capacity.